The NASA‐JAXA Global Precipitation Measurement mission – part II: New frontiers in precipitation science. (4th November 2020) - Watters, Daniel; Battaglia, Alessandro
Abstract : A Global Precipitation Measurement (GPM) mission study of Hurricane Irma 2017. The background colours represent the accumulation across the cyclone lifetime from the Integrated Multi‐satellitE Retrievals for GPM product. The dot positions represent the hurricane centre location with colours representing the Saffir‐Simpson Hurricane Scale from the National Oceanic and Atmospheric Administration IBTrACS product. 'PH' stands for pre/post hurricane status. The magenta tracks correspond to an overpass of the GPM Core Observatory; the dashed, solid and dashed‐dotted lines represent the GPM radar Ka‐band, Ku‐band and microwave imager swaths, respectively.